Implementation of Inclusive Education for Students with Hearing Impairment (Deaf): A Study in Elementary School - Hardian Mei Fajri; Asep Supena; Totok Bintoro (JIP Jurnal Ilmiah PGMI, 2024)
Inclusive education is based on the right of all learners to a quality education that meets their basic learning needs and enriches their lives. This study aims to describe the implementation of elementary school inclusive education for students with hearing loss. This research method used a qualitative descriptive approach. Data collection techniques were carried out through interviews with teachers, and observation. This research uses triangulation techniques to check the validity of the data. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The results of this study found that in the implementation of inclusive learning/education in elementary school, three important components support the academic success of learners with hearing impairments, namely: (1) the role of the teacher is to create a positive and meaningful classroom atmosphere for learners, positioning learners with hearing impairments to be considered by other classmates, not as different children; (2) the role of fellow learners in the classroom is as allies to support and help each other in academic activities; and (3) the role of parents is to provide more attention, support and time to support children's cognitive health and academic development and success.